Pathogenicity of duck plague and innate immune responses of the Cherry Valley ducks to duck plague virus - Li, Ning (Sci Rep, 2016)
Duck plague caused by duck plague virus (DPV) is an acute and contagious disease. To better understand the pathogenic mechanism of duck plague virus in ducklings, an infection experiment was performed. Our results showed that typical symptoms were observed in the infected ducklings. DPV could replicate quickly in many tissues, leading to pathological lesions, especially on the spleen. Real-time quantitative PCR demonstrated that expression of many innate immune-related genes was mostly up-regulated in the brain, and the antiviral innate immune response was established, but not sufficient to restrict viral replication. In contrast, although the expression of many major pattern recognition receptors (PRRs) increased in the spleen, the expression of most cytokines was declined. Our study indicates that DPV is a pantropic virus that can replicate rapidly in tissues, causing serious pathological lesions but the immune responses are different in the spleen and brain. To our knowledge, this is the first report to systematically explore the expression profiles of the immune genes in the DPV-infected ducks. Our data provide a foundation for further study of the pathogenicity of duck plague.